The storied self: a narrative approach to the spiritual care of the aged - Stevens, Bruce A. (Lexington Books/Fortress Academic, 2019)
The need for narrative -- Overview of the deep story -- The first gap in the life story -- Gaps in the narrative -- The God story -- Testing true and false stories -- Testing faith stories -- About the messy, problem, body, and dark stories -- Integration through story -- Designing a new story -- Performing a new story -- One from many stories.